OBJECTIVE AXIOLOGICAL SYSTEM AND INDIRECT ITERPRETATION: LARENZ vs ALEXY - NASTASIICHUK, OLEKSANDR (Ehrlich’s Journal, 2024)
The article under study deals with the two possible interpretations of the notion “objective order of values” (objektive Wertordnung), which was introduced in 1958 by the German Constitutional Court in the so-called “Lüth Decisions”. It is important that this notion has been generalized in the article as the concept “objective axiological system”. Direct axiological interpretation is represented by Karl Larenz, whereas indirect deontological interpretation – by Robert Alexy. The purpose of the article is to show, by contrasting the approaches of K. Larenz and R. Alexy, the advantages of deontological interpretation of objective axiological system over axiological interpretation. In order to achieve this goal, the article regards three issues: 1) what is the Lüth Decisions, 2) how is this concept interpreted in the jurisprudence of values by K. Larenz and in the theory of principles by R. Alexy, 3) in what ways does the deontological interpretation of the Lüth Decisions prevail over the axiological one. In its principal part, the article suggests that objective axiological system of norms is an evolutionary complement to the analytical system of norms, and this complement can have both direct and indirect interpretations. Further on, direct interpretation is reduced to the jurisprudence of values by K. Larenz, while indirect interpretation – to the theory of principles as optimization requirements by R. Alexy. Eventually, the article proves that the latter theory has at least two important advantages. In conclusion, the article claims that such concepts as “objective order of values”/“objective axiological system”, on the one hand, and the system of principles as optimization requirements, on the other hand, are functionally identical, since they (directly or indirectly respectively) supplement the analytical system of positive law with such normative elements as values (evaluation criteria, assessment) and/or principles. Deontological interpretation of objective axiological system has at least two advantages. First, it generally forms a single and homogeneous system of norms (normative-analytical system), which consists of rules as definitional requirements and principles as optimization requirements. Second, deontological interpretation, proposed by R. Alexy, aims at forming a rule that can be eventually applied in the form of a subsumption, whereas K. Larenz’s jurisprudence of values denies this possibility and offers decisions (theory of types, the concept of specific and general, weighing of values, etc.) that are less obvious and much more complex than the theory of applying (weighing) principles.